ChatGPT and Biblical Studies - McGrath, James F. 1972- (2025)
The use of computers in the study of theology has a long and positive history, yet the level of concern in response to the latest AI chatbots is understandable. This article explores how education and preaching need to adapt to this new technology and what its limitations are, as well as how it may make a positive contribution. The study concludes with a brief exploration of the kinds of sermon materials GPTs produced for the author when given prompts about the story of the Samaritan woman in John 4.
Keywords: Teaching; Preaching; Translation; Artificial Intelligence; ChatGPT